2020
DOI: 10.1007/s11145-020-10090-w
|View full text |Cite
|
Sign up to set email alerts
|

Kindergarten pre-reading skills predict Grade 9 reading comprehension (PISA Reading) but fail to explain gender difference

Abstract: One of the aims for compulsory education is to diminish or alleviate differences in children’s skills existing prior to school entry. However, a growing gender gap in reading development has increasingly been documented. Regrettably, there is scant evidence on whether differences between genders (favouring girls) have their roots in pre-reading skills or whether determining mechanisms are related to factors to do with schooling. We examined the extent to which pre-reading skills assessed in Kindergarten (age 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
1
8

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 62 publications
3
17
1
8
Order By: Relevance
“…Answers were rated on a scale from 1 to 7 (1 = rarely or never; 4 = a few times a month; 7 = every day). Previous studies showed that this measure of reading time for leisure was associated with children's RA at 8 years old (Tétreault and Desrosiers, 2014;Nanhou et al, 2016;Torppa et al, 2020;Manu et al, 2021).…”
Section: The Frequency Of Leisure Readingmentioning
confidence: 92%
“…Answers were rated on a scale from 1 to 7 (1 = rarely or never; 4 = a few times a month; 7 = every day). Previous studies showed that this measure of reading time for leisure was associated with children's RA at 8 years old (Tétreault and Desrosiers, 2014;Nanhou et al, 2016;Torppa et al, 2020;Manu et al, 2021).…”
Section: The Frequency Of Leisure Readingmentioning
confidence: 92%
“…Important indicators of linguistic and reading development include phonological awareness, letter knowledge, and rapid naming (RAN; Chall, 1996;Denckla & Rudel, 1976;Lundberg et al, 1988;Manu et al, 2020). Being able to name letters in the alphabet is known to play an important role in the first phase of reading development (Siegel, 2013).…”
Section: Background Knowledgementioning
confidence: 99%
“…This is why most of the countries emphasize on the teaching of pre reading and pre writing skills to the preprimary pupils (Zarfsaz&Yeganehpour, 2021;Osei, et al 2016). Pre reading and writing skills are considered to be essential for the academic development of pupils as well as the acquisition of reading and writing skills (Manu et al, 2021). Literature suggest that proper teaching of pre reading and pre writing skills can be effective if the teachers make use of play and song strategies (Lesser et al, 2019;Musa et al, 2012;Klimova, 2013;Mourão, 2014).…”
Section: Problem Statementmentioning
confidence: 99%
“…Pre-primary education has been presumed to have an influence on children's' literacy skills development in primary school. According to Manu et al (2021), pre-reading skills significantly predict students reading comprehension. This means that pupils who acquire pre-reading skills show significant development in reading abilities when compared to the ones without such skills.…”
Section: Introductionmentioning
confidence: 99%